Preparation and characterization of sulfonated polystyrene pore-filled electrolyte membrane by radiation induced grafting [compact disc] - 402908 Nor Aida Zubir (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Gas)) - Universiti Teknologi Malaysia, 2004